Mercado de valores mobiliários: aplicação dos princípios contratuais às relações existentes entre as empresas de capital aberto e os investidores - Amaral, Andréa Costa do (2010)
We can say that the real state and the stock markets have increasingly grown and taken unimaginable proportions in a globalization process and economic growth. In this context the investor needs to comprehend how businesses are done in this specific market, as well as if there is any or what are the protection norms for his future investment. In order to guarantee protection for the investor, Brazilian State created the Real State Stock Exchange Comission, which represents a regulatory agency for the sector which surveys an regulates everything concerned to the stock market and yet plays a sanctioning role when illicit conducts are perpetrated in these matters. There is a specific auto-regulatory system that concerns to this market with its own rules and following procedures. In the present work we studied the rules and requisites that are concerned to the companies that open their shares in the stock market exchange and the investors who seek for these shares. We assure that the relationship between the investor and the company that wishes to open its capital has a contract based nature. Thus, as a contractual relationship, we understand in this work that not only the real state stock market auto-regulation rules, but the rules and principles of the brazilian contractual and civil law should be also applied in these matters. This whole conception brings up the importance of the theme as the related judicial conflicts emerge and both set of rules can be used to solve them as well. Even if the contractual relationship between the investor and the companies has international patterns, either the real state auto-regulation rules or the brazilian civil law, rules and principles can be used to solve their conflicts in the judiciary level. Finally, this research stands for the investor who seeks to achieve the proper legal protection as his investment can now be seen as a real contract with all its terms, principles and characteristic rules.